2023
DOI: 10.2337/dc22-1830
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Predictors of Incident Diabetes: Results From the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: OBJECTIVE The plasma proteome preceding diabetes can improve our understanding of diabetes pathogenesis. RESEARCH DESIGN AND METHODS In 8,923 Atherosclerosis Risk in Communities (ARIC) Study participants (aged 47–70 years, 57% women, 19% Black), we conducted discovery and internal validation for associations of 4,955 plasma proteins with incident diabetes. We externally validated results in the Singapore Multi-Ethnic Cohort (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Our study corroborated some previously identified protein-diabetes associations, such as the associations of diabetes with TYRO3 (tyrosine-protein kinase receptor TYRO3), ARG1, SHBG, MANSC4, HP, MANBA, ABO, angiotensin-converting enzyme (ACE), ERO1-like protein beta (ERO1LB), MICB, and GSTA1. 8 , 14 The associations of some well-studied proteins, like GCKR, 5 SHBG, 16 ABO, 17 and ACE 18 with the risk of developing type 2 diabetes were also identified, which indicated a good validity of data sources used in the current analysis. However, except for ABO, ARG1, ERO1LB, GSTA1, and TYRO3, we observed weak colocalization support of the associations for other above-mentioned proteins, which implies that these associations may be influenced by linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our study corroborated some previously identified protein-diabetes associations, such as the associations of diabetes with TYRO3 (tyrosine-protein kinase receptor TYRO3), ARG1, SHBG, MANSC4, HP, MANBA, ABO, angiotensin-converting enzyme (ACE), ERO1-like protein beta (ERO1LB), MICB, and GSTA1. 8 , 14 The associations of some well-studied proteins, like GCKR, 5 SHBG, 16 ABO, 17 and ACE 18 with the risk of developing type 2 diabetes were also identified, which indicated a good validity of data sources used in the current analysis. However, except for ABO, ARG1, ERO1LB, GSTA1, and TYRO3, we observed weak colocalization support of the associations for other above-mentioned proteins, which implies that these associations may be influenced by linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 71%
“… 7 Another study with a larger sample size identified 47 proteins associated with incident type 2 diabetes after 19 years of follow-up. 8 Still, merely three associations were confirmed by Mendelian randomization (MR) analysis. 8 These findings may convey that observational studies on proteomic research in type 2 diabetes are prone to be influenced by reverse causation, as well as confounding given that the factors influencing proteomic profiles remain unestablished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 522 proteins identified in our study, 316 (60.64%) proteins were not previously reported to be associated with T2D risk (Supplementary Figure 6). We compared our findings to four published studies on proteomics and T2D incidence in European and African populations [12,13,15,16]. Of the 530 proteins that were significant at a Bonferroni threshold (approximately 1x10 -5 ) or had an FDR q-value less than 0.05 in at least one other study, 479 (90.38%) were present in our data.…”
Section: Incident T2d Association With Proteins At Baselinementioning
confidence: 88%
“…Proteins, as products of gene transcription, function as dynamic biomarkers reflecting genetic regulation and environmental changes, which can aid in pinpointing the perturbed proteins and pathways in T2D pathogenesis [10]. Large-scale population proteomic studies on plasma proteins and complex diseases, including T2D, have become possible in recent years as high-throughput proteomic profiling technologies improve [11][12][13][14][15][16]. Using the genome, Mendelian randomization (MR) uses genetic variants to assess causality and has been used to integrate the genome and proteome to reveal causal proteins and potential T2D therapeutic targets [12,13,16,17].…”
Section: Introductionmentioning
confidence: 99%